DIFFUSE LARGE CELL NON HODGKIN LYMPHOMA AT RETROBULBAR OCCULUS SINISTRA MASS - Viqa Faiqah; Nadirah Rasyid Ridha (Journal Health & Science : Gorontalo Journal Health and Science Community, 2023)
Non-Hodgkin’s Lymphoma (NHL) is a large group of malignant neoplasms originating in the lymph nodes and extra nodes of lymphoid tissues. This kind of malignancy is quite common in the world with 3% of all cancer cases. In Indonesia, NHL is the 6th most common cancer and is the third most rapidly progressive cancer after melanoma and lung cancer. The novelty in this study is diffuse large cell non hodgkin lymphoma at retrobular occulus sinistra mass. A 15-years-old boy came with complaints of a protruding left eye since 2 months ago, begin with reddish eyes which gradually enlarged and decrease of visual function. Biopsy confirmed the diagnose as a stage 2 non-Hodgkin's lymphoma with Diffuse large cells. This patient underwent a chemotherapy procedure according to the non-Hodgkin's lymphoma’s protocol for 1 year that turn out in decrease of tumor progression and good result of the chemotherapy. A case of retrobulbar mass occulus sinistra et causa non-Hodgkin's lymphoma in a 15 year old boy. Diagnose is based on history, physical examination, laboratory tests and biopsy. Treatment of this patient using chemotherapy regimens according to the non-Hodgkin's lymphoma protocol.